2010
DOI: 10.2151/jmsj.2010-202
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Compact and Sensitive Electrostatic Radon-222 Measuring System for Use in Atmospheric Observation

Abstract: A new automated 222 Rn measuring system suitable for a wide range of atmospheric observations has been developed. This system comprises a 222 Rn analyzer and an air-sampling unit, along with a pump, drying equipment, and a filter. The operation of this 222 Rn analyzer is based on an electrostatic collection method involving the use of a PIN photodiode to separately detect a particles emitted from 218 Po and 214 Po released from the decay of 222 Rn in a hemispheric air-sample chamber. The response of the 222 R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…However, for short integration times (e.g. 1 h), the detection limit can be high (160-200 mBq m −3 ; Wada et al, 2010). The direct two-filter dual-flow-loop technique reported in this study is unique with regard to its broad applicability to weather/fetch conditions and its very low detection limit at hourly temporal resolution (see Sect.…”
Section: Introductionmentioning
confidence: 93%
“…However, for short integration times (e.g. 1 h), the detection limit can be high (160-200 mBq m −3 ; Wada et al, 2010). The direct two-filter dual-flow-loop technique reported in this study is unique with regard to its broad applicability to weather/fetch conditions and its very low detection limit at hourly temporal resolution (see Sect.…”
Section: Introductionmentioning
confidence: 93%
“…Wada et al (2011) showed that the combustion-related enhancement ratio of CO to CO 2 observed at these sites depended on the emission ratio of CO to CO 2 in East Asia. In addition, Wada et al (2010) demonstrated that the enhanced 222 Rn peaks observed at MNM showed a high correlation with synoptic scale variation of CO observed simultaneously at this station. These results indicated that the emission ratios of the trace gases emitted from East Asia are conserved in the enhancement ratios reflected at these sites.…”
Section: A Wada Et Al: Evaluation Of Anthropogenic Emissions Of Carmentioning
confidence: 61%
“…The 222 Rn analyzer used in this study was developed by AIST and MRI (Wada et al, 2010) for precise measurements of atmospheric 222 Rn. It is based on the electrostatic collection method that collects positively charged progenies of 222 Rn in the sampling air on the light sensitive photodiode (PIN photodiode) for an alpha particle detector charged high negative voltage.…”
Section: Measuring Methodsmentioning
confidence: 99%
See 2 more Smart Citations